Sinergi digitalisasi dan etika kecerdasan buatan (AI) dalam tata kelola institusi islam - Hurriyah, 'Aisyah Indana Zulfa Al Hurriyah Sasa (Maliki Interdisciplinary Journal, 2026)
In today’s world, technology is developing rapidly, especially with the advent of artificial intelligence (AI) This opens up opportunities for numerous innovations, but also poses complex ethical challenges for islamic institutions. This study aims to examine how technology can be used in islamic instituitions, focusing on three main aspects: developing digital policies for education, using Generative AI to manage finances, and understanding islamic law regarding the use of AI. This study uses qualitative methods by studying existing literature and analyzing its concepts through a Maqashid Sharia system approach. The result indicate that dveloping robust digital policies for educational services in islamic universities is crucial for improving service quality and ensuring qualified graduates, provided they are supported by good infrastructure. Furthermore, the use of Generative AI can make the financial management of islamic institutions more effective and efficient by simplifying reporting and budget projections. However, the use of this technology must be in accordance with islamic values, particularly regarding the protection of property and lives, to avoid cyber risks and algorithmic bias. This study concludes that islamic institutions need to create adaptive governance systems while adhering to islamic ethics to survive in this ever-changing era.